Handbook for Career Specialization Programs - McLeod, Carmen E.; Research for Better Schools, Inc., Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
Designed for use with the Research for Better Schools experience-based career education model, this handbook offers procedures for designing and developing career specialization activities that will offer students an opportunity to learn on a one-to-one basis about one career. The first of six sections defines career specialization, provides suggestions for end products, and states the objectives of career specialization. Section 2 defines the roles of the student, career development staff, and employer. Focusing on learning activities in career specialization, section 3 serves as a guide for defining student interest, recruiting specialization sites and negotiating specializations with site personnel. The fourth section presents guidelines for preparing student learning contracts. A chart summarizing the various ways experience-based career education programs have awarded academic credit for specialization is presented in section 5. The final section focuses on the evaluation of the student's performance and end product. Appended material includes the career development student questionnaire, student interest form and questionnaire, student learning contract, student performance evaluation form, and an example career specialization program. (LRA)
Availability: Research for Better Schools, 444 North Third Street, Philadelphia, PA 19123 ($6.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: OB-NIE-78-0207.
ERIC Note: For related documents see CE 023 015, CE 023 064-066, CE 023 166, and CE 023 170-172.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Keywords: Career Awareness; Career Development; Career Education; Career Exploration; Discovery Learning; Experiential Learning; Guidelines; Interests; Learning Activities; Program Development; School Community Relationship; Secondary Education; Vocational Interests; Guides, Non-Classroom.